Un Framework para apoyar las decisiones de Outsourcing de SI / TI en Instituciones Públicas del Perú, aplicando el Proceso de Análisis Jerárquico (AHP) - Alarcón Loayza, Luis Alberto (2025)
In recent years, following the COVID-19 pandemic, the demand for outsourcing processes in Information Systems and Technology (IS/IT) has intensified globally and continues to grow, according to market studies from prestigious international entities. However, in the Peruvian public sector, decision-making regarding IS/IT outsourcing still lacks formal methodologies to properly evaluate its feasibility and risks. This article proposes a framework to support outsourcing decisions by applying the Analytic Hierarchy Process (AHP). The research, qualitative and deductive in nature, combined a literature review with the application of the AHP model in a reference public institution. The framework is structured in four phases: identification of prerequisites, definition of the decision model, risk assessment, and selection of projects to be outsourced. For validation, four projects from the National University of San Marcos were considered. The results show that the AHP model enables a more objective prioritization of projects and mitigates outsourcing risks, constituting a replicable tool to strengthen sourcing strategies in public institutions and improve IT governance.